Inhaled corticosteroid effects both eosinophilic and non-eosinophilic inflammation in asthmatic patients - Ilknur Basyigit; Fusun Yildiz; Sevgiye Kacar Ozkara; Hasim Boyaci; Ahmet Ilgazli (Hindawi Limited, 2004)
AIM: To determine induced sputum cell counts and interleukin-8 (IL-8), tumor necrosis factor alpha (TNF-α) and leukotriene B4 (LTB4) levels as markers of neutrophilic inflammation in moderate persistent asthma, and to evaluate the response to inhaled steroid therapy.